Antibacterial activity of ripe and rotten fruit Phaleria Macrocarpa (Mahkota dewa) extraction / Nur Hidayahtul Ain Ibrahim - Ibrahim, Nur Hidayahtul Ain (2018)
Many studies previously shown that Phaleria macrocarpa contain numerous antimicrobial properties from different parts of the plant. This research studied the antibacterial activity of ripe and rotten fruit extraction from Phaleria macrocarpa on Gram positive and Gram negative bacteria. The ability of fruit extract was determined to indicate the effectiveness to inhibit the growth of bacteria. Ripe and rotten fruit of P.macrocarpa was obtained and dried for 24 hours in the drying oven. Each of the fruit was grinded into fine powder. Each sample was mix with HCL and methanol for extraction and continued tested on E.coli and S.aureus. Study showed that rotten extract on E.coli have different significant value. The same result also shown by the E.coli from ripe extract. However, both rotten and ripe fruit extract towards Gram negative bacteria which is S.aureus shown no different significant value since the significant value is greater than 0.05, as the comparison on both ripe and rotten extract toward E.coli and S.aureus, rotten extract show the most effective extract. In short, Phaleria macrocarpa on both ripe and rotten fruit extract inhibit Gram negative bacteria better than Gram positive bacteria.